Elastic backscattering measurments for 6,7Li+58Ni, 6,7Li+116,120Sn, 6,7Li+208Pb at near barrier energies - Zerva, K.; et al., ... (HNPS Advances in Nuclear Physics, 2019)
We have performed, elastic backscattering measurements for the weakly bound nuclei 6,7Li on the medium and heavy mass targets 58Ni, 116,120Sn, 208Pb at sub- and near-barrier energies (0.6 to 1.3 EC.b.). Excitation functions of elastic scattering cross sections have been measured at 160O and 170O and the corresponding ratios to Rutherford scattering and relevant barrier distributions have been extracted. These measurements will complement recent work on a 28Si target for probing the potential at sub- and near barrier energies and relevant reaction mechanisms.